Cancer Chemopreventive Role of Dietary Terpenoids by Modulating Keap1-Nrf2-ARE Signaling System—A Comprehensive Update - Md Afjalus Siraj (MDPI AG, 2021)
ROS, RNS, and carcinogenic metabolites generate excessive oxidative stress, which changes the basal cellular status and leads to epigenetic modification, genomic instability, and initiation of cancer. Epigenetic modification may inhibit tumor-suppressor genes and activate oncogenes, enabling cells to have cancer promoting properties. The nuclear factor erythroid 2-related factor 2 (Nrf2) is a transcription factor that in humans is encoded by the NFE2L2 gene, and is activated in response to cellular stress. It can regulate redox homoeostasis by expressing several cytoprotective enzymes, including NADPH quinine oxidoreductase, heme oxygenase-1, UDP-glucuronosyltransferase, glutathione peroxidase, glutathione-S-transferase, etc. There is accumulating evidence supporting the idea that dietary nutraceuticals derived from commonly used fruits, vegetables, and spices have the ability to produce cancer chemopreventive activity by inducing Nrf2-mediated detoxifying enzymes. In this review, we discuss the importance of these nutraceuticals in cancer chemoprevention and summarize the role of dietary terpenoids in this respect. This approach was taken to accumulate the mechanistic function of these terpenoids to develop a comprehensive understanding of their direct and indirect roles in modulating the Keap1-Nrf2-ARE signaling system.